"Developments" at Aura: Actors, Projects and Rationales in Confrontation in an area of Environmental Protection in Belém (Pa) (Revista LIDER, 2020)
The article discusses the territory of Aurá, located in Belém (PA), its actors, relations and social conflicts, environmental and economic aspects, represented by the garbage collectors, the Municipal Government and State and Conestoga-Rovers, a company that burns gas methane produced by decomposition of the waste. The challenge is to understand how these actors socially reappropriate nature, an environmental rationality, in the sense presented by Leff (2002), exceeding the mastery of the logic of the market. The methodology used interviews and questionnaires to collect data, between July and September 2012, from the stakeholders involved in the issue. As preliminary results we note an irregularity in Aurá, that works without licensing, the poor conditions of nearby residents and scavengers, and the Conestoga company that trades carbon credits by burning methane gas. We therefore have found a fundamental disconnection between social, environmental and economic policies.